Vietnam Women’s Academy adopts gender transformative approaches developed with SAAF in its curricula and training of officials - Phuong Nguyen, Thi Minh; Galiè, Alessandra; Pazos, Mateo Cardenas; Triana Angel, Natalia (International Livestock Research Institute, 2025)
Based on the collaboration with the Gender, Youth and Social Inclusion team (AoW5) of the CGIAR Sustainable Animal and Aquatic Foods (SAAF) Science Program, the Vietnam Women’s Academy (VWA) has changed: a. one curriculum for bachelors’ degree courses and b. their training of public officials in Vietnam and Laos. VWA has integrated a new focus on gender norms and gender transformative approaches (GTAs) with a focus on livestock, into their curricula across six bachelor’s degree courses. These topics were not previously included in any of their education programs. These new courses have reached 1,284 students (70% women) and inspired an academy-level, student-led research project on gender norms, fostering a new generation of gender-aware professionals. Also, VWA utilized this curriculum in training sessions for 250 public officials from Vietnam and Laos. These activities demonstrate how AoW5 of SAAF influenced partners to transform gender norms through both academic excellence and practical professional development.